Overview of medical device regulations and recent updates - MURAKAMI, Madoka (Journal of the National Institute of Public Health, 2022)
In 2013, Pharmaceutical Affairs Law (Act No. 145 of 1960) was amended and changed its name to the Act on Securing Quality, Efficacy and Safety of Products Including Pharmaceuticals and Medical Devices. Then there was another amendment to the act in 2019. In those amendments, standalone software intended for medical use which is called Software as a medical device (SaMD) was subject to the medical device regulations and processes which enable patients to access earlier to the medical device with cutting-edge technology were enshrined in to law. The system to streamline the change process for medical devices including SaMD which have shorter product life cycle was also legalized.This report describes the overview of medical device regulations in Japan and some of the review systems adopted in the amendment of the act in 2019 including"Sakigake designation system","priority review for specific use of medical devices","conditional approval system""Post-Approval Change Management Protocol (PACMP)" (So-called IDATEN (Improvement Design within Approval for Timely Evaluation and Notice)) for early patient access. This report also overviews current efforts based on"DASH for SaMD"(DX (Digital Transformation) Action Strategies in Healthcare for SaMD) which Ministry of Health, Labour and Welfare has published in November 2020, reflecting the governmental policy to accelerate the premarket review of SaMD which is mentioned in the Basic Policy of Economic and Financial Management and Reform (decided by the Cabinet on June 18, 2021).